PENERAPAN STRATEGI CONCEPT-ORIENTED READING INSTRUCTION (CORI) DALAM MENUMBUHKAN PEMAHAMAN KESEJARAHAN SISWA DALAM PEMBELAJARAN SEJARAH (Penelitian Tindakan di Kelas XI IPA 1 SMA Negeri 14 Bandung) - Sri Wahyuni, - (2020)
This research is motivated by the lack of students' historical comprehension in learning history, which indicated by the lack of how students comprehend the text. This research discussed how to developing students' historical comprehension by using Concept-Oriented Reading Instruction (CORI) Strategy. The aim of this research are for describing the planning of implementing CORI strategy in learning history, explaining the steps to implementing CORI strategy, identifying students' historical comprehension through the implementing of CORI strategy, and describing the effort to resolved the obstacles in implementing strategi in learning history. There are four indicators of students' historical comprehension such as; 1) knowledge and understanding of historical events, 2) identify the central question of the historical narrative, 3) critical thingking to examine and utilize the knowledge of history, also 4) historical skill that can be used to study various types of informations to determine the validity of the information. Using the Classrom Action Research with Kemmis and McTaggart design research. Based on the result, the indicators of historical comprehension are 92,05% on the fourth cycle. This research is proving the application of CORI strategy could be used as a solution to developing students' historical comprehension in learning history in each cycles. Keyword: CORI Strategy, Historical Comprehension, Historical Learning.